Dosimetric parameter determination of a carbon-nanotube based miniature x-ray tube for HDR brachytherapy - Kang, Sang-Won; Chung, Jin-Beom; Eom, Keun-Yong; Song, Changhoon; Kim, In-Ah; Kim, Jae-Sung; Lee, Jeong-Woo; Cho, Woong (Frontiers in Oncology, 2025)
PurposeThis study aims to determine key dosimetric parameters of a vacuum-sealed miniature X-ray tube (mXT) equipped with a carbon nanotube field emitter for application in HDR brachytherapy.MethodsDosimetric parameters, including dose-rate constant, radial dose, and anisotropic function, were assessed 1 cm below the mXT employing EBT3 film and a custom-manufactured acrylonitrile butadiene styrene (ABS) phantom. The dose-rate constant and radial-dose functions were measured following the standard polar angles and radial distances prescribed by the AAPM TG-43 protocol. However, anisotropic function measurements were selectively conducted due to the directional dependence of Gafchromic EBT3 film when placed coplanar to the X-ray source. To minimize this effect, films were positioned 1 cm below the mXT, which restricted the measurable angular range. These parameters were also computed in both a virtual ABS and water phantom using the MCNP6.1 code. Correlation factors for different materials were obtained to adjust measured parameters in the ABS phantom to those in water, based on the calculated depth–dose curve. The dosimetric parameters were then determined by comparing the measured and calculated values.ResultsThe dose-rate constant was determined to be 1344.14 cGy·h-1·μA-1. Radial-dose functions were 0.49, 0.33, 0.22, and 0.15 at radial distances of 2.0, 3.0, 4.0, and 5.0 cm, respectively. The difference between measured and calculated radial-dose functions in water remained within 0.10, averaging 0.05. Anisotropic functions exhibited an increase with the radial distance, approaching 0° angle. Azimuthal angular dependence was deemed acceptable.ConclusionThis study successfully acquired both measured and calculated parameters for the newly developed mXT. The findings affirm that the dosimetric parameters of the mXT are within acceptable limits for clinical HDR brachytherapy applications.